Elucidating the chemical profile and biological studies of Verbascum diversifolium Hochst. extracts - Yagi, Sakina; Nilofar, Nilofar; Uba, Abdullahi Ibrahim; Caprioli, Giovanni; Mustafa, Ahmed M.; Angeloni, Simone; Koyuncu, Ismail; Seker, Fatma; Polat, Rıdvan; Supti, Sumaiya Jahan; Tasnim, Faria; Al Dhaheri, Yusra; et al. (Frontiers in Pharmacology, 2024)
The present study was designed to evaluate the chemical composition, antioxidant, enzyme inhibition and cytotoxic properties of different extracts from aerial parts of Verbascum diversifolium (family Scrophulariaceae), a plant that is native to Lebanon, Syria and Turkey. Six extracts, namely hexane, dichloromethane (DCM), ethyl acetate (EtOAc), ethanol (EtOH), 70% EtOH, and water (aqueous) were prepared by maceration. The EtOH extract was predominated by the presence of rutin (4280.20 µg g-1) and p-coumaric acid (3044.01 µg g-1) while the highest accumulation of kaempferol-3-glucoside (1537.38 µg g-1), caffeic acid (130.13 µg g-1) and 4-hydroxy benzoic acid (465.93 µg g-1) was recorded in the 70% EtOH, aqueous, and EtOAc extracts, respectively. The EtOH (46.86 mg TE/g) and 70% EtOH (46.33 mg TE/g) extracts displayed the highest DPPH radical scavenging result. Both these extracts, along with the aqueous one, exerted the highest ABTS radical scavenging result (73.03 – 73.56 mg TE/g). The EtOH and 70% EtOH extracts revealed the most potent anti-AChE (2.66 and 2.64 mg GALAE/g) and anti-glucosidase (1.07 and 1.09 mmol ACAE/g) activities. The aqueous extract was the most efficacious in inhibiting the proliferation of prostate cancer (DU-145) cells with an IC50 of 8.71 µg/mL and a Selectivity Index of 3.7. In conclusion, this study appraised the use of V. diversifolium aerial parts as a potential therapeutic source for future development of phytopharmaceuticals that target specific oxidative stress-linked diseases including diabetes, cancer, cardiovascular disease, and Alzheimer's disease among others.